Cellular therapy in musculoskeletal tissue regeneration: Perspectives on osteoarthritis and the use of mesenchymal stem cells (Research, Society and Development, 2024)
Osteoarthritis is a common and debilitating musculoskeletal condition that causes progressive degeneration of joint cartilage, resulting in pain, stiffness, and limited joint mobility. Faced with the challenges of effective osteoarthritis treatment, cellular therapy has emerged as a promising approach to promote regeneration of affected tissues. This study presents a comprehensive review of cellular therapy in osteoarthritis, highlighting key findings, challenges, and future perspectives in this area. The research was conducted through the selection and analysis of relevant studies in the PubMed, Scopus, and Web of Science databases, with a 20-year inclusion period. Primary studies were prioritized, including clinical trials, meta-analyses, randomized clinical trials, and systematic reviews. The results indicate that cellular therapy, especially the use of mesenchymal stem cells, holds potential to promote cartilage regeneration, reduce inflammation, and modulate the immune response in joints affected by osteoarthritis. However, further research is needed to optimize therapeutic strategies, overcome technical and regulatory challenges, and validate the long-term efficacy and safety of these treatments.